The Academic Scholar Award of the American Association of Plastic Surgeons. Issue 2 (February 2015) - Sweeney, Walter M.; Cederna, Paul S.; Losee, Joseph E.; Lee, W. P. Andrew; Katz, Adam J.; Rubin, J. Peter; Gosain, Arun K.
<x xml:space="preserve">Abstract</x> Background: This study evaluated the 20-year history of the American Association of Plastic Surgeons Academic Scholar Award from 1992 through 2012, to assess the program's value and justify future investment. Methods: The curricula vitae of 18 Academic Scholars who completed their award by 2012 were analyzed. Data were compiled into 5-year blocks and reviewed. Results: Award recipients has 589 grants, an average of 33 per recipient. Sixty-nine grants were active, and the recipient was the principal investigator in 61 of these grants. Active funding is 68 million. Recipients average 3.7 active grants per person, with a value of 3.8 million per grant. The average number of grants peaks at 5 to 10 years after award completion and then declines slightly to 42 at 10 to 15 years. During this time, total grant money increased from 956, 667 to 8.1 million, suggesting that senior surgeons produce more money with fewer grants. Recipients produced 2378 peer-reviewed articles, and productivity was the highest 5 to 10 years after award completion. Three hundred forty-one individuals were mentored, and each recipient mentored an average of 18 individuals. Forty-two mentees entered academics, and 32 generated extramural funding. Scholars increased mentorship activity, as demonstrated by (1) increased grants as any role, (2) increased grant funding as any role, (3) increased median number of senior author publications, and (4) mentorship activities and accomplishments of mentees. Conclusions: The Academic Scholar program met its goals based on (1) Scholars' careers, (2) increased mentorship, and (3) cost-benefit ratio of the American Association of Plastic Surgeons investment. Every 1 invested produces 70, with a return that exceeds 1000 percent.